A preparation method of manganese ferrite and its application
Manganese ferrate was prepared by using solid-phase sintering method of trimanganese tetraoxide and iron oxide, and the problems of toxic gas generation and high hardness caused by manganese and iron sulfate raw materials were solved, and high purity manganese ferrate was obtained, which was used as the positive electrode material of lithium manganese iron phosphate battery, improving the performance of the battery.
Patent Information
- Application Number
- CN202311851612.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-12-29
AI Technical Summary
In the prior art, when using sulfates of manganese and iron as raw materials to prepare lithium manganese iron phosphate batteries, toxic gas sulfur dioxide is generated, and the synthetic substance has a high hardness and is difficult to ball mill, resulting in difficulty in producing high-purity lithium manganese iron phosphate.
Manganese tetraoxide and iron oxide are used as raw materials to prepare manganese ferrate by solid phase sintering method, and the feed ratio and sintering temperature of the raw materials are adjusted to obtain manganese ferrate with a higher manganese content.
The problems of the formation of toxic gas sulfur dioxide and high hardness of the composite were solved, and high purity manganese ferrate was obtained, which was suitable for the positive electrode material of lithium manganese ferroferric phosphate batteries, and the discharge specific capacity of the battery was improved.
Smart Images

Figure BDA0004641162300000061 
Figure BDA0004641162300000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing manganese ferrite in chemical materials, and specifically relates to a preparation method of manganese ferrite and application thereof. Background Art
[0002] Lithium manganese iron phosphate battery is a new type of lithium-ion battery with advantages such as high energy density, long cycle life and good safety performance. It is widely used in electric vehicles, energy storage equipment and other fields. Lithium manganese iron phosphate can be positioned as an "upgraded version of lithium iron", combining the advantages of high safety of lithium iron phosphate and high energy density of ternary lithium materials. Theoretically, when the ratio of manganese to iron is 6:4, the performance is improved by 10% to 15% compared with lithium iron, and the performance can be improved by 21% when all manganese is replaced. Lithium manganese iron phosphate is formed by combining lithium iron phosphate and lithium manganese phosphate, fully combining the advantages of both, and has an olivine structure; lithium iron phosphate has the advantages of easy synthesis, low cost and high conductivity; lithium manganese phosphate has the advantages of high voltage platform and high energy density, which makes up for the shortcomings of lithium iron phosphate; because the radius of iron and manganese atoms is similar, they can be dissolved in any proportion, thus creating lithium manganese iron phosphate. Lithium manganese iron phosphate battery is different from ternary lithium battery and lithium iron phosphate battery. Lithium manganese iron phosphate battery is a battery formed by the change of positive electrode material. Compared with the relatively mature lithium iron phosphate battery after its return to the market, it has the advantages of high voltage, high energy density and long life, but its conductivity is low and there are still some difficulties in mass production. At present, the synthesis methods of lithium manganese iron phosphate are mainly divided into solid phase method and co-precipitation method. The co-precipitation method uses manganese source, iron source and complexing agent to co-precipitate to generate a precursor, and the precursor reacts with phosphorus source and lithium source in solid phase or liquid phase to generate lithium manganese iron phosphate, such as Chinese invention patent CN105047922A. The solid phase method uses manganese source, iron source, phosphorus source and lithium source for sintering. The process is simple, but the performance of the synthesized material is poor, so the mainstream is to use co-precipitation method. The traditional solid phase method has a simple process but the performance of the synthesized material is the worst. The performance of the liquid phase method is good, but the equipment anti-corrosion requirements cause high costs and greater pressure on environmental protection. In order to improve the performance of the material, the problem faced by the low-cost characteristics is that the use of manganese and iron sulfates as manganese sources and iron sources causes the synthesis reaction to generate toxic gas sulfur dioxide, which needs to be treated, and the synthetic manganese iron lithium oxide has a high hardness and is difficult to ball mill, which is not conducive to the generation of high-purity manganese iron phosphate. The two sulfates have different thermal decomposition temperatures, which leads to easy agglomeration when generating manganese iron oxide, increases the difficulty of ball milling and is not conducive to the generation of pure phase manganese iron oxide. In addition, the synthesis reaction time in the related art is long, the reaction temperature is high, and the purity of manganese iron oxide synthesized by the reaction of manganese salts and iron salts is relatively small, and there are also mixed phase byproducts such as iron oxide and manganese oxide. If manganese ferrite is used as a material for producing manganese iron phosphate lithium batteries, it can well solve the problem that manganese and iron sulfates are used as manganese sources and iron sources, resulting in the synthesis reaction to generate toxic gas sulfur dioxide, which needs to be treated, and the synthetic manganese iron lithium oxide has a high hardness and is difficult to ball mill, which is not conducive to the generation of high-purity manganese iron phosphate.
[0003] Manganese ferrite (MnFe2O4) is a functional material with magnetic, optical and electrical properties, which is widely used in magnetic materials, sensors, data storage and other fields. The preparation methods of manganese ferrite include coprecipitation, hydrothermal, sol-gel and solid phase sintering. Although the process of preparing manganese ferrite by coprecipitation is simple, the manganese ferrite prepared is not pure enough and often contains a lot of iron oxide impurities. Even with subsequent treatment, it is difficult to improve the purity of manganese ferrite; the hydrothermal method requires the use of organic solvents to prepare manganese ferrite, which has a high investment cost and is not conducive to industrial mass production; the sol-gel method uses a low heating temperature to prepare manganese ferrite, but the preparation process is cumbersome, the time required is long, and the materials are expensive; the solid phase sintering method is generally divided into traditional solid phase sintering and solid phase reaction sintering, respectively, using iron oxide and manganese oxide, iron powder and manganese powder mixed in a certain proportion to form a dense sintered body, but this method is not easy to master the raw material ratio and sintering temperature and time under the optimal conditions, and the sintered product often contains more manganese oxide.
[0004] Therefore, how to use existing raw materials to obtain manganese ferrite with a higher manganese content by only changing the raw material feed ratio and sintering temperature has become a problem that needs to be solved urgently.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] In view of the shortcomings in the prior art, one of the problems to be solved by the present invention is to provide a method for preparing manganese ferrite, wherein manganese ferrite is obtained by sintering manganese manganese tetraoxide and iron oxide at a specific temperature. Another problem to be solved by the present invention is to propose an application of manganese ferrite in lithium iron manganese phosphate batteries, and the prepared manganese ferrite can be used to prepare the positive electrode material of lithium iron manganese phosphate batteries, solving the problems of the generation of toxic gas sulfur dioxide and the high hardness of the synthetic lithium iron manganese oxide, which is difficult to ball mill and is not conducive to the generation of high-purity lithium iron manganese phosphate.
[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing manganese ferrite, which takes manganese tetraoxide and iron oxide as raw materials, and after high mixing, grinding, demagnetization and high-temperature calcination, naturally cools to room temperature, takes out the product, and grinds it again to obtain manganese ferrite.
[0009] Furthermore, the molar ratio of the raw materials manganese tetraoxide and iron oxide is 1:3-3:1.
[0010] Furthermore, the molar ratio of the raw materials manganese tetraoxide and iron oxide is 1:1.
[0011] Furthermore, the mixing is carried out in a dry material mixer, with uniform high mixing for 0.5-1h.
[0012] Furthermore, the calcination temperature is 780-820°C and the calcination time is 110-250min.
[0013] Furthermore, the calcination temperature is 800° C. and the calcination time is 150 min.
[0014] Furthermore, the preparation method of manganese ferrite comprises the following steps:
[0015] (1) Mix the raw materials in a molar ratio of manganese tetraoxide to iron oxide of 1:1, put them into a dry material mixer and mix them evenly for 1 hour;
[0016] (2) Grinding the mixed materials to obtain a powdered sample, and then demagnetizing it;
[0017] (3) Place the demagnetized sample into an air compressor and make it into small round cakes;
[0018] (4) The small round cakes are placed in a crucible, and the crucible is placed in a muffle furnace. The cakes are calcined for 150 min at 800° C. in a reducing atmosphere, and then naturally cooled to room temperature. Manganese ferrite is obtained after being taken out and ground.
[0019] Furthermore, manganese ferrite is prepared by the above preparation method.
[0020] Furthermore, the manganese ferrite is used in preparing the positive electrode material of lithium manganese iron phosphate battery.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) In the present invention, manganese ferrite is prepared by a solid phase sintering method using manganese tetraoxide and iron oxide as raw materials. The method is simple to operate and easy to master the raw material ratio, sintering temperature and time under optimal conditions, which is beneficial to reducing impurities of other components in the product.
[0023] (2) The sintering temperature required by the present invention is lower and the sintering time is shorter. Compared with the co-precipitation method, the particles formed have more uniform shape and particle size. Compared with the existing high-energy ball milling solid phase method, the energy consumption is lower and the production efficiency is higher.
[0024] (3) The preparation process of the present invention is simple, has good atom economy, low environmental pressure, and can be mass-produced industrially. In addition, the manganese content of the product manganese ferrite can be changed by adjusting the sintering temperature and the feed ratio, and the final preparation of the positive electrode material for lithium manganese iron phosphate battery can improve the discharge specific capacity. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0026] The raw materials used in the following examples, such as manganese tetraoxide and iron oxide, are all commercially available products; the instruments used are all equipment known to those skilled in the art unless otherwise specified.
[0027] Example 1
[0028] The material sample weighed according to the molar ratio of manganese tetraoxide to iron oxide of 1:1 is preliminarily mixed, and then the material is placed in a dry material mixer and uniformly mixed for 1 hour to obtain a mixture, and the mixture is ground to obtain a powder. The sample ground into powder is demagnetized (by magnetization reversal method), and the demagnetized sample is placed in an air compressor and pressed into small round cakes (with a diameter of 3 cm and a thickness of 0.5 cm); the prepared round cakes are placed in a corundum crucible, and then the crucible is placed in a muffle furnace, and calcined for 150 minutes at a temperature of 800°C under the protection of a reducing atmosphere, and naturally cooled to room temperature, and the solid is taken out and ground again to obtain a black solid product, namely manganese ferrite.
[0029] Example 2
[0030] The material samples weighed according to the molar ratio of manganese tetraoxide to iron oxide of 1:2 are preliminarily mixed, and then the materials are placed in a dry material mixer and uniformly mixed for 1 hour to obtain a mixture, and the mixture is ground to obtain a powder. The sample ground into powder is demagnetized (by magnetization reversal method), and the demagnetized sample is placed in an air compressor and pressed into small round cakes (with a diameter of 3 cm and a thickness of 0.5 cm); the prepared round cakes are placed in a corundum crucible, and then the crucible is placed in a muffle furnace, and calcined for 150 minutes at a temperature of 800°C under the protection of a reducing atmosphere, and naturally cooled to room temperature, the solid is taken out, and ground again to obtain a black solid product, namely manganese ferrite.
[0031] Example 3
[0032] The material sample weighed according to the molar ratio of manganese tetraoxide to iron oxide of 1:3 is preliminarily mixed, and then the material is placed in a dry material mixer and uniformly mixed for 1 hour to obtain a mixture, and the mixture is ground to obtain a powder. The sample ground into powder is demagnetized (by magnetization reversal method), and the demagnetized sample is placed in an air compressor and pressed into small round cakes (with a diameter of 3 cm and a thickness of 0.5 cm); the prepared round cakes are placed in a corundum crucible, and then the crucible is placed in a muffle furnace, and calcined for 150 minutes at a temperature of 800°C under the protection of a reducing atmosphere, and naturally cooled to room temperature, the solid is taken out, and ground again to obtain a black solid product, namely manganese ferrite.
[0033] Example 4
[0034] The material sample weighed according to the molar ratio of manganese tetraoxide to iron oxide of 2:1 is preliminarily mixed, and then the material is placed in a dry material mixer and uniformly mixed for 1 hour to obtain a mixture, and the mixture is ground to obtain a powder. The sample ground into powder is demagnetized (by magnetization reversal method), and the demagnetized sample is placed in an air compressor and pressed into small round cakes (with a diameter of 3 cm and a thickness of 0.5 cm); the prepared round cakes are placed in a corundum crucible, and then the crucible is placed in a muffle furnace, and calcined for 150 minutes at a temperature of 800°C under the protection of a reducing atmosphere, and naturally cooled to room temperature, the solid is taken out, and ground again to obtain a black solid product, namely manganese ferrite.
[0035] Example 5
[0036] The material sample weighed according to the molar ratio of manganese tetraoxide to iron oxide of 3:1 is preliminarily mixed, and then the material is placed in a dry material mixer and uniformly mixed for 1 hour to obtain a mixture, and the mixture is ground to obtain a powder. The sample ground into powder is demagnetized (by magnetization reversal method), and the demagnetized sample is placed in an air compressor and pressed into small round cakes (with a diameter of 3 cm and a thickness of 0.5 cm); the prepared round cakes are placed in a corundum crucible, and then the crucible is placed in a muffle furnace, and calcined for 150 minutes at a temperature of 800°C under the protection of a reducing atmosphere, and naturally cooled to room temperature, and the solid is taken out and ground again to obtain a black solid product, namely manganese ferrite.
[0037] Example 6
[0038] The material sample weighed according to the molar ratio of manganese tetraoxide to iron oxide of 1:1 is preliminarily mixed, and then the material is placed in a dry material mixer and uniformly mixed for 1 hour to obtain a mixture, and the mixture is ground to obtain a powder. The sample ground into powder is demagnetized (by magnetization reversal method), and the demagnetized sample is placed in an air compressor and pressed into small round cakes (with a diameter of 3 cm and a thickness of 0.5 cm); the prepared round cakes are placed in a corundum crucible, and then the crucible is placed in a muffle furnace, and calcined for 250 minutes at a temperature of 700°C under the protection of a reducing atmosphere, and naturally cooled to room temperature, and the solid is taken out and ground again to obtain a black solid product, namely manganese ferrite.
[0039] Example 7
[0040] The material sample weighed according to the molar ratio of manganese tetraoxide to iron oxide of 1:1 is preliminarily mixed, and then the material is placed in a dry material mixer and uniformly mixed for 1 hour to obtain a mixture, and the mixture is ground to obtain a powder. The sample ground into powder is demagnetized (by magnetization reversal method), and the demagnetized sample is placed in an air compressor and pressed into small round cakes (with a diameter of 3 cm and a thickness of 0.5 cm); the prepared round cakes are placed in a corundum crucible, and then the crucible is placed in a muffle furnace, and calcined for 220 minutes at a temperature of 750°C under the protection of a reducing atmosphere, and naturally cooled to room temperature, and the solid is taken out and ground again to obtain a black solid product, namely manganese ferrite.
[0041] Example 8
[0042] The material sample weighed according to the molar ratio of manganese tetraoxide to iron oxide of 1:1 is preliminarily mixed, and then the material is placed in a dry material mixer and uniformly mixed for 1 hour to obtain a mixture, and the mixture is ground to obtain a powder. The sample ground into powder is demagnetized (by magnetization reversal method), and the demagnetized sample is placed in an air compressor and pressed into small round cakes (with a diameter of 3 cm and a thickness of 0.5 cm); the prepared round cakes are placed in a corundum crucible, and then the crucible is placed in a muffle furnace, and calcined for 120 minutes at a temperature of 850°C under the protection of a reducing atmosphere, and naturally cooled to room temperature, the solid is taken out, and ground again to obtain a black solid product, namely manganese ferrite.
[0043] Example 9
[0044] The material sample weighed according to the molar ratio of manganese tetraoxide to iron oxide of 1:1 is preliminarily mixed, and then the material is placed in a dry material mixer and uniformly mixed for 1 hour to obtain a mixture, and the mixture is ground to obtain a powder. The sample ground into powder is demagnetized (by magnetization reversal method), and the demagnetized sample is placed in an air compressor and pressed into small round cakes (with a diameter of 3 cm and a thickness of 0.5 cm); the prepared round cakes are placed in a corundum crucible, and then the crucible is placed in a muffle furnace, and calcined for 110 minutes at a temperature of 900°C under the protection of a reducing atmosphere, and naturally cooled to room temperature, and the solid is taken out and ground again to obtain a black solid product, namely manganese ferrite.
[0045] Example 10
[0046] The material sample weighed according to the molar ratio of manganese tetraoxide to iron oxide of 1:1 is preliminarily mixed, and then the material is placed in a dry material mixer and uniformly mixed for 1 hour to obtain a mixture, and the mixture is ground to obtain a powder. The sample ground into powder is demagnetized (by magnetization reversal method), and the demagnetized sample is placed in an air compressor and pressed into small round cakes (with a diameter of 3 cm and a thickness of 0.5 cm); the prepared round cakes are placed in a corundum crucible, and then the crucible is placed in a muffle furnace, and calcined for 110 minutes at a temperature of 1000°C under the protection of a reducing atmosphere, and naturally cooled to room temperature, the solid is taken out, and ground again to obtain a black solid product, namely manganese ferrite.
[0047] Embodiment 11
[0048] A certain amount of manganese ferrite obtained in the above Examples 1-10 was taken respectively, dissolved in 20 mL of aqua regia, filtered, and then fixed to 100 mL. ICP detection was performed, and the test results are shown in Table 1 below;
[0049] Table 1: Comparison of the percentages of manganese and iron in the manganese ferrite obtained in Examples 1-10
[0050]
[0051]
[0052] From the results in Table 1, it can be seen that the relative percentages of manganese and iron in the manganese ferrite prepared in Examples 1-10 are compared. As the sintering temperature increases from 700°C to 1000°C, the relative percentage of manganese in the product manganese ferrite increases first and then decreases. When the sintering temperature is 800°C, the percentage of manganese in the obtained manganese ferrite product reaches the maximum, with a maximum value of 60%. And as the sintering temperature increases, the time required for sintering gradually decreases.
[0053] Comparative Examples 1-5 show that when the molar ratio of trimanganese tetraoxide to iron oxide is gradually increased from 1:3 to 3:1, as the material ratio of trimanganese tetraoxide increases, the relative percentage content of manganese in the product manganese ferrite first gradually increases and then decreases. However, when the material ratio exceeds 1:1, the trimanganese tetraoxide that has not reacted completely will generate manganese oxide at high temperature, which will reduce the percentage of manganese in the final product manganese ferrite. Therefore, the optimal molar ratio of manganese carbonate to iron oxide is 1:1, at which time the percentage of manganese in the product manganese ferrite is the largest, reaching 60%.
[0054] The present invention adopts a solid phase sintering method to prepare manganese ferrite, and by adjusting the feed ratio of manganese and iron, and by controlling the sintering temperature and the sintering time, a manganese ferrite product with a manganese content of not less than 60% is finally obtained, and the positive electrode material of a lithium manganese iron phosphate battery can be prepared, thereby improving the discharge specific capacity of the positive electrode material of the lithium manganese iron phosphate battery.
[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing manganese ferrite, characterized in that: Here are the steps: (1) Mix the raw materials in a molar ratio of manganese tetraoxide to iron oxide of 1:1, put them into a dry material mixer and mix them evenly for 1 hour; (2) Grinding the mixed materials to obtain a powdered sample, and then demagnetizing it; (3) Place the demagnetized sample into an air compressor and make it into small round cakes; (4) putting the small round cake into a crucible, placing the crucible in a muffle furnace, calcining for 150 minutes at 800° C. in a reducing atmosphere, cooling naturally to room temperature, taking out and grinding to obtain manganese ferrite; the manganese ferrite has a manganese content of not less than 60%.
2. Manganese ferrite prepared by the preparation method according to claim 1.
3. Use of the manganese ferrite according to claim 2 in preparing a positive electrode material for a lithium manganese iron phosphate battery.
Citation Information
Patent Citations
Carbon-coated lithium manganese ferric phosphoric acid cathode material and preparation method
CN105047922A
Iron oxide red powder and preparation method thereof
CN116768279A
Method for preparing lithium manganese iron phosphate, cathode material, and lithium-ion battery
US20230322557A1